Perbedaan Harga Diri dan Subjective Well-Being antara Remaja dengan Orangtua Lengkap dan Bercerai - Aminatul Masriah; Maharani Ardi Putri; Diana Rita Ari Radiaswati (Fakultas Psikologi Universitas Pancasila, 2012)
This research is aimed to examine the difference in the self-esteem and subjective well-being of the adolescents who grow up in intact families and those in divorced parents. The sample of this research is 30 adolescents who grow up in intact families as well as 30 adolescents of divorced parents, using a quota sampling technique. The researcher uses the scale of self-esteem and subjective well-being to collect the data. The researcher then uses t-test method as the technique of data analysis, the analysis shows that t-value of self-esteem variable is 1.138 (p>0.05) while the t-value of subjective well-being variable is 3.950 (p<0.05). The research shows that there is no the difference in self-esteem of the adolescents who grow up in intact families and those who grow up in divorced parents, while the research also shows that there is the significant difference in subjective well-being of these two compared subject groups.